In vitro function and in situ localization of Multidrug Resistance-associated Protein (MRP)1 (ABCC1) suggest a protective role against methyl mercury-induced oxidative stress in the human placenta - Granitzer, Sebastian; Ellinger, Isabella; Khan, Rumsha; Gelles, Katharina; Widhalm, Raimund; Hengstschläger, Markus; Zeisler, Harald; Desoye, Gernot; Tupova, Lenka; Ceckova, Martina; Salzer, Hans; Gundacker, Claudia (Archives of toxicology, 2020)
Methyl mercury (MeHg) is an organic highly toxic compound that is transported efficiently via the human placenta. Our previous data suggest that MeHg is taken up into placental cells by amino acid transporters while mercury export from placental cells mainly involves ATP binding cassette (ABC) transporters. We hypothesized that the ABC transporter multidrug resistance-associated protein (MRP)1 (ABCC1) plays an essential role in mercury export from the human placenta. Transwell transport studies with MRP1-overexpressing Madin-Darby Canine Kidney (MDCK)II cells confirmed the function of MRP1 in polarized mercury efflux. Consistent with this, siRNA-mediated MRP1 gene knockdown in the human placental cell line HTR-8/SVneo resulted in intracellular mercury accumulation, which was associated with reduced cell viability, accompanied by increased cytotoxicity, apoptosis, and oxidative stress as determined via the glutathione (GSH) status. In addition, the many sources claiming different localization of MRP1 in the placenta required a re-evaluation of its localization in placental tissue sections by immunofluorescence microscopy using an MRP1-specific antibody that was validated in-house. Taken together, our results show that (1) MRP1 preferentially mediates apical-to-basolateral mercury transport in epithelial cells, (2) MRP1 regulates the GSH status of placental cells, (3) MRP1 function has a decisive influence on the viability of placental cells exposed to low MeHg concentrations, and (4) the in situ localization of MRP1 corresponds to mercury transport from maternal circulation to the placenta and fetus. We conclude that MRP1 protects placental cells from MeHg-induced oxidative stress by exporting the toxic metal and by maintaining the placental cells' GSH status in equilibrium.
Keywords: Madin Darby Canine Kidney Cells; ATP-Binding Cassette Transporters; Animals; apoptóza; Female; buněčné linie; glutathion; buňky MDCK; oxidační stres; methylortuťné sloučeniny; Glutathione; ženské pohlaví; Apoptosis; Oxidative Stress; Immunohistochemistry; Placenta; lidé; Gene Knockdown Techniques; ABC transportéry; těhotenství; Dogs; kultivované buňky; Endothelial Cells; Multidrug Resistance-Associated Proteins; imunohistochemie; Cell Line; proteiny spojené s mnohočetnou rezistencí k lékům; transportní systémy aminokyselin; Cells, Cultured; Methylmercury Compounds; endoteliální buňky; genový knockdown; Amino Acid Transport Systems; Cell Survival; zvířata; viabilita buněk; Pregnancy; placenta; psi; Humans